2016
DOI: 10.1002/cncr.30008
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of stereotactic body radiotherapy and optional transarterial chemoembolization for solitary hepatocellular carcinoma not amenable to resection and radiofrequency ablation

Abstract: BACKGROUND: Curative treatment options for patients with early stage hepatocellular carcinoma (HCC) include resection, liver transplantation, and percutaneous ablation therapy. However, even patients with solitary HCC are not always amenable to these treatments. The authors prospectively investigated the clinical outcomes of patients who received stereotactic body radiotherapy (SBRT) for solitary HCC. METHODS: A phase 2 study involving SBRT and optional transarterial chemoembolization (TACE) was conducted in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(156 citation statements)
references
References 28 publications
9
140
2
2
Order By: Relevance
“…HepG2 Cells (5 Â 10 6 in 0.2-mL PBS) were inoculated (via subcutaneous injection) into 7-week-old BALB/c female athymic nude mice (Taconic). When tumor volumes reached 100 mm 3 , mice were randomized into 3 groups (n ¼ 8/group) and received intraperitoneal injection with lycorine (10 or 20 mg/kg/d) or vehicle every other day for 33 days. Tumor volume and body weight were monitored every 3 days.…”
Section: Xenograft Tumorigenicity Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…HepG2 Cells (5 Â 10 6 in 0.2-mL PBS) were inoculated (via subcutaneous injection) into 7-week-old BALB/c female athymic nude mice (Taconic). When tumor volumes reached 100 mm 3 , mice were randomized into 3 groups (n ¼ 8/group) and received intraperitoneal injection with lycorine (10 or 20 mg/kg/d) or vehicle every other day for 33 days. Tumor volume and body weight were monitored every 3 days.…”
Section: Xenograft Tumorigenicity Assaysmentioning
confidence: 99%
“…HCC is a heterogeneous disease originated from chronic liver diseases, such as chronic inflammation and cirrhosis. To date, the therapeutic strategy against HCC is mainly composed of resection, transplantation, local ablation, and chemotherapy (3,4). Because early symptoms of HCC are not obvious, most patients with HCC are diagnosed at advanced stages and are unsuitable for potentially curative therapies such as resection, transplantation, and local ablation (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…reported that the 3-year local control rate of liver cancer was 96.3%, the 3-year liver-related cause-specific survival rate was 72.5%, the overall survival rate was 66.7%, and toxicity was tolerable [9]. The use of SABR is expected to increase as this method advances in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For tumors ≥2 cm, there was decreased FFLP for RFA compared with SBRT (HR, 3.35; p = 0.025). Takeda et al [44] conducted a phase II study, treating 90 CP A and B score patients with a solitary HCC lesion up to a diameter of 4 cm, unsuitable for resection and RF with SBRT and optional TACE. Three-year LC rate and OS was 96.3% and 66.7% (95% CI, 56.3–75.6%) respectively.…”
Section: Discussionmentioning
confidence: 99%